Hydrodynamic pattern investigation of ethanol droplet train impingement on heated aluminum surface - Kanbur, Baris Burak (2022)
Steady-state hydrodynamic patterns of ethanol droplet train impingement on the heated aluminum surface is investigated in the surface temperature range of 80°C–260°C using two different Weber numbers (We) of 618 and 792. Instead of a vertical train impingement, the droplet train is sent to the aluminum surface with an incline of 63 degrees. Changes in the spreading length are observed at different surface temperatures for two different We values, which are obtained by using two different pinholes with 100 and 150 μm diameters. The greatest spreading length is seen at the lowest surface temperature (80°C) and it continuously decreases until the surface temperature of 200°C. Above 200°C, the spreading length remains stable which is most probably because of the Leidenfrost effect. The spreading lengths of the experiments with 100 μm are 46.4% smaller than the experiments with 150 μm. Also, splashing angles are observed for both We values. The ranges of splashing angle observations are 140°C–200°C and 170°C–185°C for We values of 792 and 618, respectively.